(untitled) (CAHIERS MAGELLANES-NS, 2024)
Purpose: Pregnancy is a joyful phase in the life of any woman. But due to various physical and mental changes during this phase, all the members of his family have a great impact on his behaviour. Therefore, the aim of the present research was to study the participation of pregnant women in Tapovan centres and type of family on their home environment. Methods : This research was an ex-post facto type of research. In which 120 pregnant women were selected through a Probability Purposive Sampling Technique. The Home Environment scale for Married Women (HEMW) Scale developed by Dr A.N. Prajapati and Vrunda Thakar (2024) was used for data collection. The 'f-test' has been used to statistically analyse the data. Finding: At the end of the present study, it was found that the pregnant women who were participated in the Tapovan Centre had an increase in home environment compared to the non-participated pregnant women. While no significant difference was observed in terms of type of family.